Analisis Sebaran Serabut Vaskular dan Sifat Fisis Batang Kelapa Sawit Varietas DxP pada Berbagai Zona dan Ketinggian Batang - Ayu Wulandari; Erwinsyah Erwinsyah (Pusat Penelitian Kelapa Sawit, 2020)
In an attempt to obtain a homogenous board density from the palm trunk, this research was carried out to analyze the distribution of vascular bundles and the physical properties of the oil palm trunk (moisture content, density, and specific gravity) in various zones and trunk heights. Oil palm trunk samples were used from 29 years old palm (Planted on 1991) which acquired from Aek Pancur Experimental plantation, Indonesian Oil Palm Research Institute (IOPRI). The oil palm trunk sample was cut based on the trunk zones (peripheral, central, and inner), and trunk heights (1, 2, 3, 4, 5, 6, 7 m). The observed parameters were vascular bundles, moisture content, density, and specific gravity. The results showed that the highest number of vascular bundles in the peripheral zone (73.66 vb/cm2). In addition that, the highest density and specific gravity also found in peripheral zone with an average 0,73 gram/cm3 and 0.53, whereas the highest moisture content was found in the inner zone with an average value 141%(w/w). Furthermore, the statistical analysis ((ANOVA and regression test (R2)) in this study showed that the trunk zone factor was more significant than the trunk height for all observed parameters (distribution of vascular bundles, moisture content, density and specific gravity).